Effects of low-frequency rTMS combined with speech and language therapy on Broca’s aphasia in subacute stroke patients - Gan, Li; Huang, Litao; Zhang, Yin; Yang, Xin; Li, Lijuan; Meng, Lijiao; Wei, Quan (Frontiers in Neurology, 2024)
Introduction: Broca's aphasia is a crushing syndrome after stroke. Although there are multiple therapies, the recovery of a considerable number of patients is still not ideal.Repetitive transcranial magnetic stimulation (rTMS) combined with speech and language therapy has been a promising combination regimen in recent years. However, the efficacy and persistent effects thereof remain unclear. We aimed to determine the immediate and long-term effects of rTMS combined with speech and language therapy on subacute stroke patients with Broca's aphasia and explore relevant mechanisms in the picture-naming task via functional near-infrared spectroscopy (fNIRS).This was a prospective clinical study. In accordance with the inclusion criteria, 18 patients with post-stroke were recruited and randomly divided into either the rTMS group or the sham-rTMS group. Patients in both groups received lowfrequency rTMS therapy for 20 minutes a day and then speech and language therapy for 30 minutes a day, 5 days a week, for a total of 4 weeks. Two groups of patients underwent the language and cognitive assessments. Meanwhile, we collected fNIRS task state data while naming images before and after 4 weeks of treatment. There was a statistically significant difference between the two groups in language and cognitive functions. Independent sample t-tests also showed that until 4 weeks after the end of treatment, there were significant differences in information volume and naming scores between the two groups. Three months after the end of treatment, there were significant differences in information volume, naming, AQ and repetition scores . In the picture-naming task, fNIRS analysis found that in the rTMS group after treatment, the activation in the left superior temporal gyrus (STG), middle temporal gyrus (MTG), premotor cortex (PM), supplementary motor area (SMA), pars triangularis Broca's area, and dorsolateral prefrontal lobe (DLPFC) decreased (P < 0.05).The language function of patients was improved after 4 weeks of treatment, and there was a long-term effect (3 months follow-up), especially in naming gains.Moreover, we found that rTMS could downgrade the activation level in the left MTG, STG, PM and SMA, DLPFC, and pars triangularis Broca's area.